Theoretical Approaches to Deviant Behavior - Popa, Ecaterina; Iurchevici , Iulia (Journal of Danubian Studies and Research, 2021)
This article, entitled “Theoretical Approaches to Deviant Behavior”, highlights the main theories of deviant behavior. Sociological approaches can identify personality traits that, in certain contexts of social learning and experience, predispose certain individuals to turn their attention to delinquent acts.